The Influence of Entrepreneurship Education on Entrepreneurial Intention: A Literature Review - Arief Budiman; Lily Harlina Putri (Journal Business Administration: Entrepreneurship and Creative Industry, 2026)
Entrepreneurship education has become a strategic instrument in fostering entrepreneurial intention among university students globally. This literature review examines the influence of entrepreneurship education on entrepreneurial intention through the lens of the Theory of Planned Behavior (TPB). A systematic review of 15 selected empirical studies published between 2015-2025 was conducted, focusing on diverse educational contexts across Asia, Europe, Africa, and South America. The findings reveal that entrepreneurship education significantly and positively influences entrepreneurial intention, with this relationship mediated by TPB components (attitude, subjective norms, and perceived behavioral control) and entrepreneurial self-efficacy. Moderating factors include prior entrepreneurial experience, academic major, gender, and psychological capital. The study provides practical implications for curriculum development and policy-making in entrepreneurship education, while highlighting the need for context-specific approaches. Future research should explore longitudinal effects and the role of digital entrepreneurship education in shaping entrepreneurial intentions